How Can You Reduce Flooding Damage to Vegetable Crops? - Yuncong Li; Renuka Rao; Stewart Reed (EDIS)
Several management practices have been reported to help crops partially or entirely overcome flood damage. For example, the application of nitrogen (N) fertilizers overcomes N deficiency, while natural or synthetic hormones are used to correct hormone imbalances, and the addition of fungicides help control soil-borne pathogens. We recently conducted a flooding experiment with bush bean, cowpea, and sweet corn. This article recommends some practices to alleviate flooding damage of vegetables. This document is SL 206, one of a series of the Soil and Water Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: August 2003.